Factors associated with trunk skeletal muscle thickness and echo intensity in young Japanese men and women - Funa Kitagawa; Hiroshi Akima; Noriko Ishiguro-Tanaka (PLoS ONE, 2025)
The present study examined factors associated with trunk skeletal muscle thickness (MT, an index for the amount of skeletal muscle) and echo intensity (EI, an index for the content of non-contractile tissue, such as intramuscular adipose tissue) in young Japanese men and women in consideration of habitual dietary intake. Healthy men (n = 26) and women (n = 24) aged 20 to 26 were enrolled. Trunk MT and EI were evaluated using ultrasound imaging at the height of the 3rd lumbar vertebra. In addition to morphological variables, brachial-ankle pulse wave velocity (baPWV) and blood properties (e.g., triglycerides, total cholesterol, and fasting blood glucose) were measured. Habitual dietary intake was also evaluated by a self-administered diet history questionnaire. The results obtained for young men revealed significant correlations between trunk MT/body mass1/3 and the percentages of energy from polyunsaturated fatty acids (rs = 0.476, p <0.05) and carbohydrates (rs = -0.402, p <0.05). Trunk EI significantly and positively correlated with the percentage of energy from saturated fatty acids (rs = 0.397, p <0.05). In young women, trunk EI showed a significant and positive correlation with baPWV (rs = 0.504, p <0.05). These results suggest that the effects of habitual dietary intake on trunk skeletal muscle differ between young men and women.